SEBUAH STUDI KASUS: EKSPLORASI MODEL PICTURE AND PICTURE DALAM UPAYA GURU MENCAPAI TUJUAN PEMBELAJARAN IPA - Rosfiani, Okta; Anggraeni, Anisa; Hasan, Nailah Najwa; Thoharroh, Ridho Nur; Nadia, Nadia; Rahman, Ridwan Nur; Hermawan, Cecep Maman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Learning is an important process that involves individuals with the guidance of a teacher. The picture and picture type cooperative learning model is an approach using pictures as a medium. Execution, the images are paired or sequenced in a logical sequence. This method helps students understand the material more easily, because information is presented through visual media making complex concepts simpler, easier to understand. This study employs a hybrid classroom action research design strategy with the goal of raising learning standards. Two cycles of classroom action research are conducted, with four phases in each cycle: preparation, activity, observation, and reflection. When it's pre-cycle, an evaluation of science learning in grade II of SDN Tanjung Barat 09 was carried out to assess the initial condition of students, especially learning outcomes. The evaluation showed that most students still failed in learning and had not reached the KKM. 26 students, consisting of 14 boys and 12 girls, the lowest score was 40, the highest score reached 90. As many as 57.70% of students scored below the KKM, while 42.30% of students managed to score above the KKM. ABSTRAKPembelajaran adalah proses penting yang melibatkan individu dengan panduan seorang guru. Model pembelajaran kooperatif tipe picture and picture adalah suatu pendekatan menggunakan gambar sebagai media. Pelaksanaan, gambar dipasangkan atau diurutkan bentuk urutan yang logis. Metode ini membantu siswa memahami materi lebih mudah, karena informasi disajikan melalui media visual membuat konsep yang rumit menjadi lebih sederhana, mudah dipahami. Penelitian ini menggunakan pendekatan campuran desain penelitian tindakan kelas bertujuan meningkatkan mutu pembelajaran. Penelitian tindakan kelas dilaksanakan dua siklus, setiap siklus melibatkan empat tahap perencanaan, tindakan, pengamatan, refleksi. Pada tahap pra-siklus, dilakukan evaluasi pembelajaran IPA di kelas II SDN Tanjung Barat 09 nilai kondisi awal siswa, terutama hasil belajar. Evaluasi menunjukkan Sebagian besar siswa masih gagal dalam belajar belum mencapai KKM. 26 siswa, terdiri dari 14 laki-laki dan 12 perempuan, nilai terendah 40, nilai tertinggi mencapai 90. Sebanyak 57,70% siswa nilai di bawah KKM, sedangkan 42,30% siswa berhasil nilai di atas KKM.